A New Kind of Weak Solution of Non-Newtonian Fluid Equation. (13th July 2017) - Zhan, Huashui; Xu, Bifen
Abstract : If the non-Newtonian fluid equation with a diffusion coefficient is degenerate on the boundary, the weak solution lacks the regularity to define the trace on the boundary. By introducing a new kind of weak solutions, the stability of the solutions is established without any boundary condition.